2005
DOI: 10.1021/jp044301x
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization Reactions on Ni2P(001) and α-Mo2C(001) Surfaces:  Complex Role of P and C Sites

Abstract: X-ray photoelectron spectroscopy and first-principles density-functional calculations were used to study the interaction of thiophene, H(2)S, and S(2) with Ni(2)P(001), alpha-Mo(2)C(001), and polycrystalline MoC. In general, the reactivity of the surfaces increases following the sequence MoC < Ni(2)P(001) < alpha-Mo(2)C(001). At 300 K, thiophene does not adsorb on MoC. In contrast, Ni(2)P(001) and alpha-Mo(2)C(001) can dissociate the molecule easily. The key to establish a catalytic cycle for desulfurization i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
261
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 299 publications
(276 citation statements)
references
References 47 publications
9
261
1
Order By: Relevance
“…Although Liu et al has found that P in phorsphide plays a role to activate the catalysis through both ligand and ensemble effects, [21,22] it is expected that phosphorus termination will eliminate the coordinatively unsaturated sites on the metal atoms, which are the positions for chemical bond formation with reactants. Meanwhile, the phosphorus layer will also provide protection for the bulk material in the commonly employed procedure of passivation, where the freshly synthesized material is exposed to a dilute stream of oxygen to allow handling at ambient conditions [23].…”
Section: What Is Observed In Stm?mentioning
confidence: 99%
“…Although Liu et al has found that P in phorsphide plays a role to activate the catalysis through both ligand and ensemble effects, [21,22] it is expected that phosphorus termination will eliminate the coordinatively unsaturated sites on the metal atoms, which are the positions for chemical bond formation with reactants. Meanwhile, the phosphorus layer will also provide protection for the bulk material in the commonly employed procedure of passivation, where the freshly synthesized material is exposed to a dilute stream of oxygen to allow handling at ambient conditions [23].…”
Section: What Is Observed In Stm?mentioning
confidence: 99%
“…In addition, since the P 2 atoms possess a slight negative charge (-0.07e), they provide additional sites for 3 hydrogen adsorption [15,36]. This theoretical proposal has also been supported by 4 studies of the electronic structure of Ni2P [35].…”
mentioning
confidence: 72%
“…Further analysis showed that the Ni3P-P structure accounts for 80±10% of the total surface, while the remainder (about 20%) is 1 composed of an uncovered Ni3P2 structure [29]. This model structure therefore explains 2 the apparent contradiction between theoretical predictions [15] and experimental STM using angle-resolved photoelectron spectroscopy (ARPES) [32,33,35] and observed a 5 Ni 3d-P 3p hybrid band (determined to be the main band) around 0-4 eV and a satellite 6 band at 8 eV in the photoelectron(PE) spectra. The satellite band was attributed to the 7 two-hole bound state resulting from the resonance behavior of the Ni 3d photoemission.…”
mentioning
confidence: 94%
See 2 more Smart Citations